Управління маркетинговими витратами підприємства як основний інструмент його розвитку - Могила, І.С. (Культура народов Причерноморья, 2013)
Зростання значущості маркетингової сфери для сучасних компаній визначає як актуальність
управління даним видом діяльності в цілому, так і управління витратами на її здійснення. Незважаючи
на наявність значної кількості методів управління витратами, розробки з обґрунтованого їх вибору на
сьогодні майже відсутні. Управління витратами має бути гнучким, відповідати змінам у діяльності
підприємства та враховувати особливості об’єкта – витрат. Рост значимости маркетинговой сферы для современных компаний определяет как
актуальность управления данным видом деятельности в целом, так и управление затратами на ее
осуществление. Несмотря на наличие значительного количества методов управления затратами,
разработки по обоснованного их выбора на сегодня почти отсутствуют. Управление затратами
должно быть гибким, соответствовать изменениям в деятельности предприятия и учитывать
особенности объекта – расходов. Recently, the Ukrainian economy has fully realized the importance of marketing for enterprise
development, in particular its role in increasing sales, profits, expanding customer base, etc. Growing
importance of marketing areas for modern company defines as the relevance of data management activity in
general and administration costs of its implementation. Despite the presence of a significant amount of
management costs, the development of an informed choice on their now almost absent. According to the author,
a qualified analysis of marketing costs of structural elements is relevant and necessary to the successful
operation of a modern enterprise. It is necessary to carry out marketing activities adapted to the crisis. The
heads of marketing services are often able to develop analytical skills for quantitative assessment of
management of marketing activities and the costs of its implementation. In this context, the decision taken in
marketing without having the necessary data and expert estimates. Given this situation, most recently in the
economic sphere is increasingly growing demand for marketing based on the database and calculations.Cost
management has to be flexible and respond to changes in the enterprise and tailored to suit the object - cost.